2013
DOI: 10.1111/imig.12052
|View full text |Cite
|
Sign up to set email alerts
|

Returnees' Perspectives on Their Re‐migration Processes

Abstract: The return of refugees and migrants back to their country of origin is an important topic on the agenda of Western European governments, as return is considered as the most “durable solution” for the “refugee problem”, and as an instrument with which to tackle “illegal” migration. However, these migration policies generally lack a clear evidence base, as little studies have focused on returnees' current living situations and on their perspectives on the re‐migration process. In this paper we therefore try to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Moreover, local partners in the home countries also indicated that the allocated reintegration budget for individual returnees was insufficient, certainly when the support was aimed at setting up a business or at providing assistance to vulnerable people (Caritas ), a picture confirmed by individual returnees (Lietaert et al . ). The evaluation further concluded that access to the support was inadequately regulated.…”
Section: Assisted Voluntary Return: the Case Of Belgiummentioning
confidence: 97%
“…Moreover, local partners in the home countries also indicated that the allocated reintegration budget for individual returnees was insufficient, certainly when the support was aimed at setting up a business or at providing assistance to vulnerable people (Caritas ), a picture confirmed by individual returnees (Lietaert et al . ). The evaluation further concluded that access to the support was inadequately regulated.…”
Section: Assisted Voluntary Return: the Case Of Belgiummentioning
confidence: 97%
“…Despite the adoption of repatriation as a durable solution to global migration crisis, research exploring the repatriation process is scarce (Kibreab, 2003;Lietaert et al, 2013;Ruben et al, 2009). Gillespie, Peltzer, and Maclachlan (2009) outline the three main reasons for the dearth of research on repatriation:…”
Section: Research On the Repatriation Processmentioning
confidence: 99%
“…Of specific concern, many repatriation programs provide limited information about living conditions in the country of origin. Further, most programs focus on financial assistance, paying little attention to the psychosocial needs of returnees (Lietaert et al, 2013;Ruben et al, 2013). This narrow definition of what returnees need means that NGOs and public agencies can only "play a modest role in facilitating social cohesion upon return" (Ruben et al, 2009, p. 929).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations